BMP‐9‐induced osteogenic differentiation of mesenchymal progenitors requires functional canonical Wnt/β‐catenin signalling - Tang, Ni (J Cell Mol Med, 2008)
Bone morphogenetic protein 9 (BMP‐9) is a member of the transforming growth factor (TGF)‐β/BMP superfamily, and we have demonstrated that it is one of the most potent BMPs to induce osteoblast differentiation of mesenchymal stem cells (MSCs). Here, we sought to investigate if canonical Wnt/β‐catenin signalling plays an important role in BMP‐9‐induced osteogenic differentiation of MSCs. Wnt3A and BMP‐9 enhanced each other’s ability to induce alkaline phosphatase (ALP) in MSCs and mouse embryonic fibroblasts (MEFs). Wnt antagonist FrzB was shown to inhibit BMP‐9‐induced ALP activity more effectively than Dkk1, whereas a secreted form of LPR‐5 or low‐density lipoprotein receptor‐related protein (LRP)‐6 exerted no inhibitory effect on BMP‐9‐induced ALP activity. β‐Catenin knockdown in MSCs and MEFs diminished BMP‐9‐induced ALP activity, and led to a decrease in BMP‐9‐induced osteocalcin reporter activity and BMP‐9‐induced expression of late osteogenic markers. Furthermore, β‐catenin knockdown or FrzB overexpression inhibited BMP‐9‐induced mineralization in vitro and ectopic bone formation in vivo, resulting in immature osteogenesis and the formation of chondrogenic matrix. Chromatin immunoprecipitation (ChIP) analysis indicated that BMP‐9 induced recruitment of both Runx2 and β‐catenin to the osteocalcin promoter. Thus, we have demonstrated that canonical Wnt signalling, possibly through interactions between β‐catenin and Runx2, plays an important role in BMP‐9‐induced osteogenic differentiation of MSCs.